Value of Computed Tomography-Based Three-Dimensional Pre-operative Planning in Cup Placement in Total Hip Arthroplasty With Dysplastic Acetabulum. Issue 7 (3rd October 2019) - Wu, Peihui; Liu, Qiaoli; Fu, Ming; Zhang, Zhiqi; He, Suiwen; Liao, Weiming; Kang, Yan
Abstract: Objects : To investigate the value of CT-based 3D templating software for pre-operative planning in patients with acetabular dysplasia undergoing total hip arthroplasty (THA) with a minimum follow-up of 2 years. Methods : We performed a retrospective review of a single surgeon's cohort of patients with Crowe I to III developmental dysplastic hip (49 hips in 41 patients) who underwent cementless primary THA and were available for follow-up at a mean of 2.7 years after THA. We analyzed the accuracy of cup size prediction, the reliability of pre- and post-operative cup orientation and position of reconstructed rotation center using CT-based 3D templating software. Post-operative Harris Hip Score and lower limb discrepancy was obtained at the last follow-up. Results : The sizes of 71% of the cup components (35/49) were estimated exactly, and 100% of the cup size estimates were accurate to within one-cup size. There was good reproducibility of pre- and post-operative position of reconstructed rotation center (correlation coefficient r  = 0.396 for vertical position, p  = 0.005; r  = 0.326 for horizontal position, p  = 0.024). There was no substantial agreement between the planned acetabular orientation and that measured post-operatively (correlation coefficient –0.174 for inclination and 0.045 for anteversion). There were 44 (90%) excellent or good results according to HHS. Seven patients (14%) reported lower limb discrepancy. Conclusions : Pre-operative CT-based 3D templating made it possible to predict accurate cup size and achieve reproducible cup position in patients with dysplastic acetabulum. The reproducibility of cup orientation could not be demonstrated in this study.